Back Cover: Mechanotropic Elastomers (Angew. Chem. Int. Ed. 39/2019). Issue 39 (23rd August 2019) - Donovan, Brian R.; Fowler, Hayden E.; Matavulj, Valentina M.; White, Timothy J.
Abstract : Strain‐induced liquid crystallinity dramatically improves the toughness of elastomeric polymer networks. In their Communication onpage 13744 ff., T. J. White et al. describe the mechanotropic phase transition of thiol‐ene photopolymers from a disorganized, isotropic state, to an organized, liquid crystalline state. Under stress, the liquid crystals reorient with the applied stress tensors resulting in significant strain hardening while maintaining rapid elastic recovery.